Environmental and economic sustainability of the Mediterranean Diet. (December 2014) - Germani, Alessia; Vitiello, Valeria; Giusti, Anna Maria; Pinto, Alessandro; Donini, Lorenzo Maria; del Balzo, Valeria
Abstract The Mediterranean diet (MD) has been proposed as a healthy dietary pattern for disease prevention. However, little information exists on the cost and on the environmental impact of such a dietary model. We compared the environmental impact and the costs of the current food consumption pattern of the Italian population and the Mediterranean model in order to investigate its overall sustainability. The environmental impact was calculated on the basis of three indexes, i.e. Carbon, Ecological and Water Footprint. The costs (Euro) per person of the MD and of the current Italian household food expenditure were considered on a weekly basis according to the 2013 data from the Observatory prices and tariffs of the Ministry of Economic Development and the service SMS consumers of the Ministry of Agriculture, Food and Forestry. The MD resulted to produce a lower environmental impact than the current food consumption of the Italian population. The monthly expenditure of the MD is slightly higher in the overall budget compared to the current expenditure allocated to food by the Italian population, but there is a substantial difference in the distribution of budget according to the different food groups.